A1.14 Characterisation and activation of dendritic cell subsets within the inflammed synovium of rheumatoid arthritis patients. (13th February 2015) - Canavan, M; O'Rourke, M; Orr, C; Veale, DJ; Fearon, U
Abstract : Introduction : Dendritic cells (DC) are a heterogeneous population of professional antigen presenting cells. Myeloid and plasmacytoid DC represent the two major DC subsets and can be distinguished based on their morphology, function and expression of surface markers. In this study we compared the percentage and maturation status of myeloid versus plasmacytoid DC at the site of inflammation in RA compared to systemic circulation. Methods: RA synovial tissue biopsies obtained at arthroscopy were digested using the GentleMACs system. The RA synovial cells along with synovial fluid mononuclear cells and whole blood were phenotyped for myeloid DC (CD11c, HLADR, CD141 and CD1c) plasmacytoid DC (CD123, HLADR) activation markers (CD80, CD83 and CD40) and intracellular cytokines (IL-10) using multicolour flow cytometry. To assess the effect of the synovial microenvironment on DC maturation, RA synovial tissue explants were cultured for 24 h allowing spontaneous secretion of pro-inflammatory mediators into the medium (conditioned media). Monocyte derived DC (MoDC) were then cultured in the presence of RA explant conditioned media and expression of DC maturation markers was analysed by flow cytometry. Results: A significant decrease in circulating CD11c mDC in RA peripheral blood compared to age matched HC was demonstrated (p < 0.05). The expression of CD40 on pDC in RA patients was significantly increased compared to HC (p < 0.001). CD40 and CD80 on mDC was significantly increased in synovial tissue and synovial fluid compared to that of matched peripheral blood (all p < 0.05). MoDC cultured in the presence of RA explant conditioned media had an increased percentage of CD83 positive cells, with a significant increase in CD80 expression compared to basal control medium (p < 0.05). Explant conditioned media also induced IL-10 production in MoDC as demonstrated by an increase in the percentage of intracellular IL-10 positive CD11c cells. Conclusion: DC have a more mature phenotype in the synovial tissue compared to that in synovial fluid or peripheral blood. Given that there are also lower circulating levels of DC in RA patients compared to controls and that RA explant media can activate MoDC, our data suggests that DC are recruited to the joint and this unique inflammatory microenvironment induces a program of DC maturation and activation.